Factors Influencing Students In Behavioring Healthy At Boarding Schools Batang Hari District - Syahirah Salawah; Puspita Sari; Silvia Mawarti Perdana; La Ode Reskiaddin; Ismi Nurwaqiah Ibnu; Solihin Sayuti (International Journal Of Health Science, 2023)
Causes of diseases such as scabies or scabies are still commonly found in students who are caused by students who often exchange clothes, towels and other toiletries, wash clothes that are not clean, and wear clothes that are still wet/damp. The purpose of this study was to determine the factors that influence the behavior of students in healthy behavior at Pondok Pesantren, Batang Hari Regency. This research is a quantitative study with a cross-sectional approach. This research was conducted at the Irsyadul Ibad Islamic Boarding School, Batang Hari Regency. The sample of this research was 95 MTs and MAs students out of 634 MTs and MAs students. The results of the study are that it is known that the proportion of students' behavior in the formation of healthy students at the Irsyadul Ibad Islamic Boarding School, Batang Hari Regency in 2022, has unhealthy behavior of 54.7%, poor knowledge (52.6%), and has good teacher support. (57.9%). The analysis shows that the risk factors for the behavior of healthy students are knowledge (PR=7.012; 95% CI: 2.836-17.338) and teacher/ustadz support (PR=3.668; 95% CI: 1.526-8.815. Based on the research results it is hoped that Islamic boarding schools can take action prevention in the form of periodic health checks for students and pesantren employees to detect various diseases early and increase the role of the teacher/ustadz as role models for students so that they not only direct but also set a good example, especially regarding the practice of healthy behavior.